Hiperurisemia Pada Kehamilan dan Diabetes Gestasional - Irene Maria Elena; Marshell Tendean; El Nissi; Guntur Darmawan (Jurnal Kedokteran Meditek, 2019)
This review aims to determine the metabolic effect of hyperuricemia in pregnant woman, especially those with gestational diabetes mellitus (GDM). In women, the serum uric acid level is lower compared to men of similar age. The value is related to higher estrogen concentration to increase uric acid clearance. Hyperuricemia already established as independent risk factors for metabolic syndrome and cardiovascular disease (CVD) as well as type 2 Diabetes Mellitus (DM). Asymptomatic hyperuricemia in non-pregnant adult women will increase insulin resistance due to oxidative stress, and production of inflammatory cytokine (tumor necrosis factor-a), which inevitably increases blood sugar level. Uric acid level and serum creatinine is lower in normal pregnancy due to increased renal clearance and the uricosuric effect of estrogen. Hyperuricemia is one of the contributing factors associated with insulin resistance among pregnancy instead direct effect of placental hormones. Earlier in the first trimester of pregnancy, the risk for GDM is increased. However, the causal effect of uric acid levels on DM still requires further study .